Illustrating a Pauline Imperative (Phlm. 17): Προσλαμβάνω in P.Mur. 2.115 - Cole, Zachary J. (Journal for the study of the New Testament, 2022)
This article draws attention to a neglected extrabiblical use of the verb προσλαμβάνωin a documentary text, a Jewish deed of marriage from the early second century CE (P.Mur. 2.115), and suggests its significance for understanding Paul’s appeal to Philemon on behalf of Onesimus. Προσλαμβάνω is Paul’s first imperative in his letter to Philemon (Phlm. 17), and many commentators understand it as part of a commercial idiom (‘to take as a business partner’), whether literally or metaphorically. It is argued here that such a reading is unlikely given three factors: the newly attested context of προσλαμβάνω, the predominance of kinship language in Philemon, and the underlying theme of reconciliation.